Socio-Economic Impact of Homestay: A case study of Tharu Homestay Patalganga, Birendranagar 3, Surkhet - Devkota, Bipana (Prajnik Bimarsha प्राज्ञिक विमर्श, 2024)
Homestay tourism has been emerging as a form of sustainable tourism in many rural areas as a community development program in Nepal. The entire activities from the particular location have been integrated as a major component of rural tourism in homestay programs.To examine the socio-economic status of homestay owner. This study having the objective to explore the cultural practices of Tharu community, examine the socio-economic status of homestay owner describe the demographic pattern of the study area. Tharu community from Patalganga has been operating homestay programs where guests are offered only basic facilities i.e. normal bed just as the host sleep in their own bed, local food as host normally eat, and unique traditional hospitality with different cultural and natural beauties of particular area. Local cultural activities, traditional lifestyle of host, local tests can be experienced by guests taking part in a homestay program.Tharu people are rich in culture, have their own language, custom, and culture. This Patalganga community homestay perform the following cultural dance to entertainment the tourists like circle dance, stick dance and sakhiyadance. There are some challenges for doing home stay business in Patalganga village. The qualitative characteristics of social capitals such as road, transportation, energy, communication, security, are not supportive to the homestay. Homestay in Patalganga has created an alternative source of income for the concern family of the homestay operators. However, the families face the internal and external problems in the entire homestay. Homestay is a very effective tourism tool for economic sustainability, and natural sustainability of rural community by preserving the local tradition and culture.